Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 48267 by maxmathsup by imad last updated on 21/Nov/18

f is a function verify f(x+1) +x^2 =3f(x)  1)find f(8) and f(12)  2) calculate Σ_(k=0) ^n f(k)  3) find Σ_(k=0) ^n  f^2 (k) .

fisafunctionverifyf(x+1)+x2=3f(x)1)findf(8)andf(12)2)calculatek=0nf(k)3)findk=0nf2(k).

Commented by maxmathsup by imad last updated on 22/Nov/18

2) we have f(x+1)−f(x)=−x^2  +2f(x) ⇒  Σ_(k=0) ^n (f(k+1)−f(k))=−Σ_(k=0) ^n  k^2  +2Σ_(k=0) ^n f(k) ⇒  f(n+1)−f(0) =−((n(n+1)(2n+1))/6) +2Σ_(k=0) ^n  f(k) ⇒  2Σ_(k=0) ^n f(k)=f(n+1)−f(0)+((n(n+1)(2n+1))/6)   ⇒  Σ_(k=0) ^n  f(k) =(1/2){ f(n+1)−f(0)+((n(n+1)(2n+1))/6)}

2)wehavef(x+1)f(x)=x2+2f(x)k=0n(f(k+1)f(k))=k=0nk2+2k=0nf(k)f(n+1)f(0)=n(n+1)(2n+1)6+2k=0nf(k)2k=0nf(k)=f(n+1)f(0)+n(n+1)(2n+1)6k=0nf(k)=12{f(n+1)f(0)+n(n+1)(2n+1)6}

Commented by maxmathsup by imad last updated on 22/Nov/18

1)let suppose f polynomial ⇒f(x)=ax^2  +bx+c ⇒  a(x+1)^2  +b(x+1) +c +x^2 =3(ax^2  +bx+c) ⇒  a(x^2  +2x+1)+bx+b +c +x^2 −3ax^2 −3bx−3c =0 ⇒  ax^2  +2ax +a  −2bx +(1−3a)x^2  +b−2c =0 ⇒  (1−2a)x^2  +(2a−2b)x +a+b−2c =0 ⇒  1−2a =0 and 2a−2b =0 and a+b−2c =0 ⇒  a =(1/2) ,b=a ,c =((a+b)/2) ⇒ a=(1/2) , b=(1/2) , c=(1/2) ⇒  f(x)=(1/2) x^2  +(1/2) x+(1/2) ⇒f(8) =(8^2 /2) +(8/2) +(1/2) =32 +4 +(1/2) =36 +(1/2) =((73)/2)  f(12)=((12^2 )/2) +((12)/2) +(1/2) =((144)/2) +6 +(1/2) =78 +(1/2) =((157)/2)  2) Σ_(k=0) ^n f(k) =(1/2) Σ_(k=0) ^n k^2  +(1/2) Σ_(k=0) ^n  k +(1/2)Σ_(k=0) ^n (1)  =(1/2) ((n(n+1)(2n+1))/6) +(1/2) ((n(n+1))/2) +(1/2)(n+1)  =((n(n+1)(2n+1))/(12)) +((n(n+1))/4) +((n+1)/2) .

1)letsupposefpolynomialf(x)=ax2+bx+ca(x+1)2+b(x+1)+c+x2=3(ax2+bx+c)a(x2+2x+1)+bx+b+c+x23ax23bx3c=0ax2+2ax+a2bx+(13a)x2+b2c=0(12a)x2+(2a2b)x+a+b2c=012a=0and2a2b=0anda+b2c=0a=12,b=a,c=a+b2a=12,b=12,c=12f(x)=12x2+12x+12f(8)=822+82+12=32+4+12=36+12=732f(12)=1222+122+12=1442+6+12=78+12=15722)k=0nf(k)=12k=0nk2+12k=0nk+12k=0n(1)=12n(n+1)(2n+1)6+12n(n+1)2+12(n+1)=n(n+1)(2n+1)12+n(n+1)4+n+12.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com